Diálogos entre arte e moda: a apropriação da performance como potência crítica e transformadora na Moda - Silveira, Lara Souza e Silva Amaro da (Universidade do Vale do Rio dos Sinos, 2020)
This work examines the process of flexibilization of the borders between the fields of art and fashion, through their collaborations in the course of history. More specifically, it seeks to recognize the ways in which fashion appropriates the principles of Performance as a hybrid and political language in the production of shows that accompany fashion collections. The study initially presents a contextualization of artistic movements, in modernity and post-modernity, highlighting the disciplinary contaminations that have occurred. Furthermore, it brings a historical-conceptual approach about Performance, notably identifying the role of the costume and the political dimension of the ephemeral character of the event, based on the analysis of performative creations by Marina Abramovic, Carolee Schneeman, Francis Alÿs and Anthea Hamilton. Next, the study contemplates the analysis of seven fashion shows, by the creators Kanye West, Gareth Pugh, Thom Browne, Ronaldo Fraga, Alexander McQueen, Hussein Chalayan and Jum Nakao seeking to identify the performative power of the models' actions, the scenery, the light, the soundtrack, etc. Thus highlighting the critical political power that is added to the collections of clothing. The research carried out contributed significant elements to the foundation of the fashion brand Huile sur Toile, its first collection and its presentation format.
Keywords: Arte contemporânea; Moda; Performance; Desfile; Contemporary art; Fashion; Performance; Fashion Shows